(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
It takes a huge effort to achieve success in integrating prisoners back into society, which is rather typical of penal institutions worldwide. In my study, I am trying to find answers to the question, whether motivating prisoners to study is a successful way of becoming a valuable member of society. To reach a conclusion, it is important to examine both the personality (EPQ) and the learning strategies (Kozéki-Entwistle’s Learning Orientation Questionaire) of the prisoner, and only according to the results can the most appropriate educational and pedagogical methods be worked out. The dimensions of personality which predict one’s criminal traits showed significant differences between the captives as anticipated, but the learning orientation did not differ in the experimental group as expected.